2018
DOI: 10.1002/path.5090
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mitochondrial biogenesis and paradoxical inhibition of lactate dehydrogenase mediated by 14‐3‐3η in oncocytomas

Abstract: Oncocytomas represent a subset of benign pituitary adenomas that are characterized by significant mitochondrial hyperplasia. Mitochondria are key organelles for energy generation and metabolic intermediate production for biosynthesis in tumour cells, so understanding the mechanism underlying mitochondrial biogenesis and its impact on cellular metabolism in oncocytoma is vital. Here, we studied surgically resected pituitary oncocytomas by using multi-omic analyses. Whole-exome sequencing did not reveal any nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
5
19
0
Order By: Relevance
“…In general, PRL-PA, GH-PA, and GH-PRL-PA showed increased levels of glutamine and α-KG, suggesting powerful anaplerosis of glutamine. Alanine and pyruvate were increased, suggesting that pyruvate was repurposed to alanine synthesis from ATP production, as has previously been found in oncocytoma [10]. Citruline and ornithine were also found to be increased in these pituitary adenomas.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In general, PRL-PA, GH-PA, and GH-PRL-PA showed increased levels of glutamine and α-KG, suggesting powerful anaplerosis of glutamine. Alanine and pyruvate were increased, suggesting that pyruvate was repurposed to alanine synthesis from ATP production, as has previously been found in oncocytoma [10]. Citruline and ornithine were also found to be increased in these pituitary adenomas.…”
Section: Discussionsupporting
confidence: 70%
“…Pituitary adenoma cells are suggested to undergo significant metabolic reprogramming due to their aberrant hormone production, and these metabolic alterations, in turn, may influence the progression of the tumor [9]. For instance, we previously demonstrated that pituitary oncocytoma, a specific subtype of pituitary adenoma with significant mitochondrial hyperplasia, reprogrammed its metabolism by suppressing glycolysis to facilitate mitochondrial biogenesis [10]. However, the metabolic characteristics of other subtypes of pituitary adenomas are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles were excluded because they provided proteomics data (57, 58) and another article was excluded, evaluating compounds with a molecular weight greater than 1,500 Da (59). A study that evaluated other types of pituitary tumors (60) and a review (61) were also excluded. Finally, 18 studies enrolling 241 patients with PA were eligible for our review (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The study on SDH subunit B (SDHB) (+/–) mice finds that SDHx-deficiency is a main initiator to result in the cascade of molecular events for the formation of pituitary adenomas (46). The whole-exome sequencing analysis of pituitary oncocytomas found mitochondrial DNA mutations, respiratory complex I dysfunction, and reductions of lactate and lactate dehydrogenase A (LDHA) (48). Besides glycometabolism change, lipid metabolism is also alerted in pituitary adenomas.…”
Section: Mitochondrial Dysfunction-mediated Reprogramming Energy Metamentioning
confidence: 99%